Detection of Periodic Acid – Schiff (PAS) in Gastric Mucosa of an Ulcer Model Treated with Manila - Syamsu Rijal; Edward Pandu Wiriansya; Muhammad Fatahila SR (Fakultas Kedokteran Universitas Muslim Indonesia, 2026)
Background: With the practical benefit of being less expensive than immunohistochemistry, periodic Acid – Schiff (PAS) histochemistry may reveal pathological alterations in the stomach mucosa and detect tissue carbohydrates, glycogen, and neutral mucopolysaccharides. Objective: To find out how Manilkara zapota (sapodilla) extract affects ethanol-induced gastric ulceration and to compare the PAS staining of healthy and ulcerated gastric mucosa. Methods: Wistar rat gastric tissue paraffin blocks from ethanol-ulcer groups with and without sapodilla extract were used in an experimental histochemical study. Sections were stained with H&E and PAS , and PAS features were evaluated using semi-quantitative scoring (0-3) using Shapiro-Wilk and Kruskal-Wallis (p<0.05). Results: Although the Pass-positive mucosal length showed a tendency to increase the higher-dose groups, the difference was not statistically significant (Kruskal – Wallis test, p=0.487; p>0.05) and was accompanied by considerable inter-individual variability. In contrast, lesion scores differed significantly among groups (Kruskal-Walls test p=0.026; p<0.05), with healthy animals consistently exhibiting a score of 0.00±0.00, whereas the ulcer-induced groups demonstrated higher lesion scores. Conclusion: PAS-based metrics indicate a potential mucosal-defense recovery trend with higher-dose sapodilla extract. However, the effect was not statistically confirmed, indicating the need for additional dosing/time point optimization and complementary results.